PersonAut: A Personas Model for People with Autism Spectrum Disorder - Melo, Áurea Hileia da Silva; Cabrejos, Luis Jorge Henrique Rivero; dos Santos, Jonathas Silva; Barreto, Raimundo da Silva (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Personas has been an important support mechanism in interfaces design. They represent, hypothetically, behavior synthesis, main characteristics, motivations and expectations of real users. Through Personas, empathy can be generated between interface designers and future software end-users. However, when these end users are autistic, this challenge is even bigger due to the lack of specific knowledge of some designers / developers on the autism subject. Another reason is the fact that low functioning autistic users (the audience selected for this research) have difficulty expressing themselves verbally. This work presents the PersonAut, which is a specific Personas Model for autistic individuals. Our goal is to support the designer / developer in the interface design activity so that they can create empathy in order to meet the needs of the autistic users. The main contribution of the PersonAut is to make the personas design faster and easier, in the context of software development for autistic people, through the use of diverse and specialized data sources for autistic individuals.